2017
DOI: 10.1084/jem.20161160
|View full text |Cite
|
Sign up to set email alerts
|

Design and crystal structure of a native-like HIV-1 envelope trimer that engages multiple broadly neutralizing antibody precursors in vivo

Abstract: Induction of broadly neutralizing antibodies (bNAbs) to HIV would be a major advance toward an effective vaccine. A critical step in this process is the activation of naive B cells expressing bNAb precursors. Medina-Ramírez et al. developed a BG505 SOSIP.v4.1-GT1 trimer that activates bNAb precursors in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
221
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 156 publications
(232 citation statements)
references
References 93 publications
6
221
0
2
Order By: Relevance
“…Their value is that they serve as a template for structure-guided design efforts that are intended to increase the affinity of Env binding; and as a device to measure the outcome of the engineering efforts. Most of the work in this area to date has been carried out using constructs based on gp120 monomers such as the engineered outer domain (eOD) or the 426c gp120-core families of proteins (193195 197199). The design of these constructs generally involves deleting variable loops and/or glycan sites to increase the accessibility of the CD4bs, which is consistent with their targeted focus on the CD4bs family of bNAbs (193195 197199).…”
Section: Lineage Vaccines Based On Native-like Trimersmentioning
confidence: 99%
See 1 more Smart Citation
“…Their value is that they serve as a template for structure-guided design efforts that are intended to increase the affinity of Env binding; and as a device to measure the outcome of the engineering efforts. Most of the work in this area to date has been carried out using constructs based on gp120 monomers such as the engineered outer domain (eOD) or the 426c gp120-core families of proteins (193195 197199). The design of these constructs generally involves deleting variable loops and/or glycan sites to increase the accessibility of the CD4bs, which is consistent with their targeted focus on the CD4bs family of bNAbs (193195 197199).…”
Section: Lineage Vaccines Based On Native-like Trimersmentioning
confidence: 99%
“…Accordingly, our group used structural and other insights to engineer germline-targeting (GT) SOSIP trimers so that they would engage multiple gl-bNAbs in vitro and, by extension, in vivo (200). The most advanced of the new trimers is BG505 SOSIP.v4.1-GT1, which was based on the stabilized SOSIP.v4.1 construct described above (123).…”
Section: Lineage Vaccines Based On Native-like Trimersmentioning
confidence: 99%
“…In addition to eOD-GT8, other germline-targeting immunogens are being developed, including a core gp120 derived from a clade C Env, 426c, which binds VRC01-class germline precursors and primes germline receptor-expressing B cells in vivo [30,34], and modified versions of the BG505 SOSIP.664 trimer, which can bind multiple bnAb germline specificities [35] (Figure 1B). Overall, these strategies aim to activate VRC01-like precursor B cell receptors (BCRs) with a germline-targeting immunogen, followed by boosting with more native-like Env molecules to shepherd Ab responses along favorable bnAb developmental pathways [2933].…”
Section: Approaches To Design Immunogens Capable Of Inducing Hiv Bnabsmentioning
confidence: 99%
“…The use of naturally existing or artificially created glycan holes on Env trimer immunogens to increase accessibility of immunoquiescent epitopes or to improve germline Ab binding has also been extended to the CD4bs bnAb epitope [35,40,41]. However, the glycan shield protects the underlying protein from immune recognition, therefore these immunogens may also increase accessibility of immunodominant, non-bnAb epitopes.…”
Section: Approaches To Design Immunogens Capable Of Inducing Hiv Bnabsmentioning
confidence: 99%
“…For example, many patients that develop bNAbs have circulating virus missing key glycans. It has been hypothesized that the induction of bNAbs could be achieved by the use of immunogens primers that help expand B-cell linages corresponding to the desired bNAbs [8286]. Glycosylation analytics have shown that deletion of multiple glycans has minimal effect of neighboring glycans and potentially multiple holes can be incorporated into a single immunogen without adversely affecting the remaining glycan-dependent epitopes [79].…”
Section: Expert Commentarymentioning
confidence: 99%